2019
DOI: 10.1177/2192568219878418
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fondaparinux Following Elective Lumbar Spine Surgery Is Associated With a Reduction in Symptomatic Venous Thromboembolism

Abstract: Study Design: Retrospective cohort study. Objective: To assess the impact of fondaparinux on venous thromboembolism (VTE) following elective lumbar spine surgery in high-risk patients. Methods: Matched patient cohorts who did or did not receive inpatient fondaparinux starting postoperative day 2 following elective lumbar spine surgery were compared. All patients received 1 month of acetyl salicylic acid 325 mg following discharge. The primary outcome was a symptomatic DVT (deep vein thrombosis) or PE (pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…None - - - Fourman et al. [39] 1. Aspirin 59.0±14.5 - 30.8±7.7 Thoracolumbar, lumbar, lumbosacral 2.Aspirin+Fondaparinux 61.7±13.0 - 31.3±6.7 Zervos et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…None - - - Fourman et al. [39] 1. Aspirin 59.0±14.5 - 30.8±7.7 Thoracolumbar, lumbar, lumbosacral 2.Aspirin+Fondaparinux 61.7±13.0 - 31.3±6.7 Zervos et al.…”
Section: Resultsmentioning
confidence: 99%
“…Mean patient age ranged from 47 to 66 years [28 , 31] among the 7 studies that reported average age for the entire sample [14 , 25 , [27] , [28] , [29] , [30] , [31] . Most patients were women in 8 of the 13 studies that reported sex [25 , 27 , 28 , 30 , 33 , 34 , 38 , 39] . The average BMI was 29.3, although sample-wide BMI averages were only reported in 5 (26.3%) studies [14 , 27 , 29 , 31 , 34] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its pentose structure significantly increases the affinity of antithrombin (AT), which specifically binds to the activation site of antithrombin through its non-covalent bond, resulting in the rapid inhibition of activated coagulation factor X, which in turn reduces the production of prothrombin and fibrin formation. 15 , 16 This results in rapid inhibition of activated factor X, thereby reducing thrombin production and fibrin formation. Unlike UFH and LMWH, sodium sulfadiazepoxide is not expected to bind to platelet factor IV and does not cross-react with plasma from patients with heparin-induced thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%